Sensitive, high-strain, high-rate bodily motion sensors based on graphene-rubber composites - KHAN, UMAR; COLEMAN, JONATHAN (My University, 2014)
Monitoring of human bodily motion requires wearable sensors which can detect position, velocity and acceleration. They should be cheap, lightweight, mechanically compliant and display reasonable sensitivity at high strains and strain-rates. No reported material has simultaneously demonstrated all the above requirements. Here we describe a simple method to infuse liquid-exfoliated graphene into natural rubber to create conducting composites. These materials are excellent strain-sensors displaying 104-fold increases in resistance and working at strains exceeding 800%. The sensitivity is reasonably high with gauge factors of up to 35 observed. More importantly, these sensors can effectively track dynamic strain, working well at vibration frequencies of at least 160 Hz. At 60 Hz, we could monitor strains of at least 6% at strain rates exceeding 6000 %/s. We have used these composites as bodily motion sensors, effectively monitoring joint and muscle motion as well and breathing and pulse.
PUBLISHED
Keywords: human bodily motion; human bodily motion